Critical review of chemical properties of biochar as a component of growing media - Prasad, Munoo; Tzortzakis, Nikos G. (My University, 2021)
The objective of this review is to critically asses the chemical characterization of biochar when it is used as a component in growing media and indicate the recommend parameters which could improve its use as component of growing media. In some earlier work on biochar little attempt was made to characterize the biochar and plant growth trials were done on an empirical basis. However, even recently, in growing trials biochar is chemically characterized only for pH, electrical conductivity (EC) and total macro and micronutrients. Only limited papers have presented available (extractable) nutrients. This is surprising since biochar can contain significant amounts of extractable nutrients and adjusting for this would be in our opinion important as it is unclear whether positive or negative response of plants is due to these or due to intrinsic properties of biochar such as specific surface area or nutrients. The methods used for pH and EC determination however have been numerous, from saturation paste extract, press extract, pour through method, various water extracts (1:1.5, 1:5, 1:10, 1:100, 2:1) and some on weight/volume and some on volume/volume ratio. Obviously, these methods will give different values especially regarding EC. In general, pH adjustment of peat by biochar has been suggested. However, it misses the point that peat, woodfibre and coir not only need pH adjustment but also require adequate levels of Ca and Mg, the uptake which can be exacerbated by high levels of K present in most biochars. Regarding available nutrients again there is a plethora of tests used, mostly water extraction often done on the same extract as for pH and EC. However, it has been shown that the CAT extractable method is closely related to plant uptake of N and P in peat/biochar media probably because it takes into account the strong buffering ability of biochar. In any case it is important to know precisely the available nutrient content in biochar for nutrient management as biochar can be a significant source of nutrients (often depending on feedstock and processing conditions). Only few papers have considered this response. It has been also shown recently that different fractions of biochar can contain different levels of macronutrients, and this has hardly been taken into account. We will show that biochar addition at low rates can reduce the EC in fertilized peat composted greenwaste (CGW) and spent mushroom compost. The reduction in EC was related to the specific surface area of the biochar. Very preliminary results also showed that addition of biochar can improve the seedling vitality index in “phytotoxic” composted green waste.
Keywords: CAT extract; Electrical conductivity; Extraction ratio; PH; Phytotoxicity; Surface area; Total macronutrients